2009
DOI: 10.1111/j.1365-2710.2009.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially severe drug interactions in elderly outpatients: results of an observational study of an administrative prescription database

Abstract: Purpose: To estimate the prevalence of potentially severe drug-drug interactions (DDIs) and their relationship with age, sex and number of prescribed drugs. Methods: We analysed all prescriptions dispensed from 1 January 2003 to 31 December 2003 to individuals aged 65 or more registered under the Local Health Authority of Lecco, a northern Italian province with a population of almost 330 000 persons. Elderly who received at least two co-administered prescriptions were selected to assess the presence of DDIs. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
77
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 35 publications
14
77
4
2
Order By: Relevance
“…Our findings regarding strong association of pDDIs with long hospital stay and taking increased number of drugs; and insignificant association with gender are consistent with other studies [5,6,8,9]. According to our findings, there was no significant relationship between old age and pDDIs that is inconsistent with other studies [5,[7][8][9][10]. The possible reason for this inconsistency might be the small proportion of old age patients in our study population, i.e., 41(10 %) patients were of age 46 -60 years and only 7(2 %) patients were older than 60 years ( Table 1).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our findings regarding strong association of pDDIs with long hospital stay and taking increased number of drugs; and insignificant association with gender are consistent with other studies [5,6,8,9]. According to our findings, there was no significant relationship between old age and pDDIs that is inconsistent with other studies [5,[7][8][9][10]. The possible reason for this inconsistency might be the small proportion of old age patients in our study population, i.e., 41(10 %) patients were of age 46 -60 years and only 7(2 %) patients were older than 60 years ( Table 1).…”
Section: Discussioncontrasting
confidence: 54%
“…Prevalence of potential DDIs (pDDIs) in hospital settings has been estimated in some recent studies to be in the range of 27.8 to 51.4 % [2][3][4]. Old age, taking increased number of medications, long hospital stay, gender and comorbid conditions have been reported as common risk factors for DDIs [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The present results indicated that the sex was not associated with the occurence of potential DDIs. These results were expected, given that there was no statistical significant difference between the sex and the number of clinical significant potential DDIs [27,46]. While, Cruciol-Souza et al identified female sex as a predictor of potential DDIs in hospitalized Brazilian patients [25].…”
Section: Patient Characteristic Predictorsmentioning
confidence: 80%
“…Additionally, the frequency study of potential DDIs at geriatric outpatient in 6 European countries showed that there were differences in frequency, as well as in the type of potential DDIs [23]. By study of predictors to DDIs was also observed variability, those which are patient characteristics as well as those which are therapy characteristics [20][21][22][24][25][26][27][28][29][30][31][32]. Differences in healthcare settings, registered and reimbursed pharmaceutical specialities can contribute to different utilization patterns of prescription drugs.…”
mentioning
confidence: 99%
“…[5][6][7]9,12,[15][16][17] Hence, we can say that pDDI are more common in elderly probably due to age related physiological, pharmacokinetic and pharmacodynamic changes.…”
Section: Discussionmentioning
confidence: 99%